PerlakuanAkuntansiAkadMurabahahBerbasis Margin Pada Masa Pandemi Covid-19 Berdasarkan PSAK No.102 Pada Studi Kasus Bank Syariah Indonesia (Ex.Bank Syariah Mandiri) - Sri Wulan Sari; sri rahayu; Syamsul Effendi (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2022)
This study aims to determine the correct margin calculation during the Covid-19 pandemic as well as the appropriateness of the murabahah margin treatment at Bank Syariah Indonesia Ex-Bank Syariah Mandiri Medan Branch. This type of  used a qualitative method with a descriptive approach. The object of this study is Bank Syariah Indonesia Ex-Bank Syariah Mandiri Medan Branch, which is located at Jalan Jend. AhamdYani, No.100, Kesawan, Kec. Medan Bar, Medan City. To obtain research data using interview and observation methods to one sources and documentation in installment data and financial reports from the Bank Syariah Indonesia Ex-Bank Syariah Mandiri website. The results show that Bank Syariah Indonesia Ex-Bank Syariah Mandiri Medan Branch that the accounting trearment stated in PSAK No. 102. And the impact that occurred on Bank Syariah Mandiri Ex-Bank Syariah Mandiri KC Medan is racing to customers who experience bad credit, but the financial performance Bank Syariah Indonesia Ex-Bank Syariah Mandiri Medan Branch Office declared healthy and stable.